Development of Stretchable, Self-Healing Polyvinyl Neodecanoate and Its Nanocomposites with MWCNT for Semiconducting Tape Applications - Priya K.; Shankar U.; Majhi J.; Singh M.; Singh B.P.; Bandyopadhyay A. (My University, 2025)
This article reports the development of a self-healing and self-adhesive homopolymer of vinyl neodecanoate (VNDc) using a bulk polymerization process. The obtained homopolymer PVNDc is found to have a subzero glass transition temperature (Tg) of −3 °C and an optical transparency comparable to that of inorganic glass. Moreover, a series of copolymers of VNDc with methyl methacrylate (MMA) are prepared using a solution polymerization process to understand the effect of the second comonomer on the self-healing mechanism, adhesion, and various other properties. Since PMMA is a rigid and transparent polymer, the homopolymer PVNDc is modified with this comonomer to improve the toughness of the soft, stretchable homopolymer backbone. With the introduction of MMA with VNDc, the stretchability, self-healing, and adhesion properties were found to disappear due to the substitution of a longer pendant group by a smaller one, disrupting the interlocking of tertiary carbons present at the long-chain end of the VNDc monomer residue in the homopolymer backbone and reduction in the van der Waal interaction when MMA is introduced in place of VNDc, respectively. The PVNDc homopolymer is a sticky adhesive material that, on further solution blending with different wt % of conductive fillers of MWCNT, shows bulk electrical conductivity of 9.6 × 10-4 S/cm (semiconducting) to fabricate a stretchable semiconductive tape. A PVNDc is a superstretchable, self-healing, and adhesive material that heals itself without external stimuli like pressure, temperature, and cross-linking agents. This matrix property might find its potential application in various flexible devices, such as semiconductive adhesives in electronic circuits and semiconducting tapes. © 2024 American Chemical Society.